Sustainable livelihood along major rivers: the need for new model and extension's response to riverside development - Md Yassin, Sulaiman; Mohamed Shaffril, Hayrol Azril; Hassan, Md. Salleh; Othman, Mohd Shahwahid; Abu Samah, Asnarulkhadi; Abu Samah, Bahaman (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
Many large rivers in developing countries have been well utilised as inland waterways as well as the source of many opportunities for sustainable livelihood. In Malaysia, there is a dire lack of inland waterway as a means of transportation and results in an opportunity cost to communities living along the rivers. This paper examines the feasibility of developing such an inland waterway linking Pahang River emptying into the South China Sea and the Muar River meeting the Straits of Malacca. Focussed Group Interviews amongst stakeholders and an initial survey of the communities living along the two rivers has been conducted. This paper discusses the findings of the initial study of a sample of the community members, which shall explore the quality of life index, the income generating activities, the social and economic connections of respondents to the river, the media they use to seek the development information and their assessment and future outlook of such an inland waterway in their daily lives. A new model of riverside development focussing on sustainable livelihood shall be formulated. The emergent role of extension in such a new model of regional and riverside development shall be proposed and discussed.